Gestión Financiera en el Área Administrativa del Comando de Policía en la Ciudad de Babahoyo Sub Zona 12 - Contreras Sipion, Dayanna Isabel (2018)
Financial Management is one of the fundamental components in development processes. The management of a company's financial information must be timely, accurate, reliable and accessible in order to obtain relevant conclusions that contribute to the decision-making on a specific topic. This case study was prepared according to the problem of Financial Management in the Administrative Area of ​​the Babahoyo Police Command. The Police Command Babahoyo Sub - Zone Los Rios N ° 12 is located in the streets General Barona and Olmedo from which provides the police services of the Province of Los Ríos (except the canton Quevedo) is kept to provisions of the community in general when the help and intrusion of the police personnel is required.